Low Ligation Plus High Dissection Versus High Ligation of the Inferior Mesenteric Artery in Sigmoid Colon and Rectal Cancer Surgery: A Meta-Analysis - Yin, Tzu-Chieh; Chen, Yen-Cheng; Su, Wei-Chih; Chen, Po-Jung; Chang, Tsung-Kun; Huang, Ching-Wen; Tsai, Hsiang-Lin; Wang, Jaw-Yuan (Frontiers in Oncology, 2021)
Background Whether high or low ligation of the inferior mesenteric artery (IMA) is superior in surgery for rectal and sigmoid colon cancers remains controversial. Although several meta-analyses have been conducted, the level of lymph node clearance was poorly defined. We performed a meta-analysis comparing high and low ligation of the IMA for sigmoid colon and rectal cancers, with emphasis on high dissection of the lymph node at the IMA root in all the included studies. Methods PubMed, MEDLINE, and EMBASE databases were searched to identify relevant articles published until 2020. The patient’s perioperative and oncologic outcomes were analyzed. Statistical analysis was performed using the statistical software RevMan version 5.4. Results A total of 17 studies, including four randomized control trials, published between 2011 and 2020 were selected. In total, 1,846 patients received low ligation of the IMA plus high dissection of lymph nodes (LL+HD) and 2,648 patients received high ligation of the IMA (HL). LL+HD was associated with low incidence of anastomotic leakage (P < 0.001), borderline long operative time (P = 0.06), less yields of total lymph nodes (P = 0.03) but equivalent IMA root lymph nodes (P = 0.07); moreover, LL+HD exhibited noninferior long-term oncological outcomes. Conclusion In comparison with HL, LL+HD was an effective and safe oncological procedure for sigmoid colon and rectal cancers. Therefore, to ligate IMA below the level of left colic artery with D3 high dissection for sigmoid colon and rectal cancers might be suggested once the surgeons are familiar with this technique. Protocol registration This meta-analysis was registered on INPLASY (registration number 202190029).